Cult of war - Elena Markus; Nina Frolova (Footprint)
The Main Cathedral of the Russian Armed Forces in Kubinka near Moscow is a quintessential example of the post-Soviet populist ideology, representating a mixture of ostensibly religious values with multiple secular cult objects.